PRAKTIK PENGAWASAN RAPERDA DAN PERDA SERTA UPAYA REKONSTRUKSI PENGUJIANNYA SESUAI AMANAT UUD NRI TAHUN 1945 - Umbu Rauta (Masalah-Masalah Hukum, 2015)
This study aims to assess and analyze the practice of monitoring the current draft legislation and regulation enactment of Law No. 32 of 2004 in conjunction with Law No. 28 of 2009, and efforts to reorganize the (reconstruction) testing system suitable draft legislation and regulations mandated by the Constitution of 1945. The method used in this research is juridical empirical data sources focusing on primary data supported secondary data. Collecting data through interviews and field observationsare supported by the literature study. Based on the results of research that reviewing local regulations and local regulation bill containproblematic, that the level of normative and practical. At thenormative level, there isa difference between setting the cancellation regulations of Law No.32 of 2004 juncto Law No. 23 of 2014by theArticle 24A of the 1945 Constitution. Inpractical level the problematic appears with regard to the scope of the evaluation of draft legislation, the standard of review, the legalform of the review results, follow-upreview, and implementation of filing and testing.Therefore, the system needs to reconstruction of reviewing local regulations and local regulations bill to complywiththe mandate of the 1945 Constitution. Reconstruction concerning the types of review of the local regulations and local regulation bill, and procedural law in local regulation review.Penelitian ini bertujuan untuk mengkaji dan menganalisis praktik pengawasan raperda dan perda saat berlakunya UU No. 32 Tahun 2004 juncto UU No. 28 Tahun 2009, dan upaya untuk mengatur kembali (rekonstruksi) sistem pengujian raperda dan perda yang sesuai amanat UUD 1945. Metode yang digunakan dalam penelitian ini adalah metode yuridis empiris dengan sumber data berfokus pada data primer yang didukung data sekunder. Pengumpulan data melalui wawancara danpengamatan lapangan yang didukung dengan studi kepustakaan. Berdasarkan hasil penelitian bahwa pengujian rancangan peraturan daerah dan peraturan daerah mengandung problematika, baik padatataran normatif dan praksis. Pada tataran normatif, ada perbedaan pengaturan pengujian dan pembatalan perda antara UU No. 32 Tahun 2004 juncto UU No. 23 Tahun 2014 dengan Pasal 24A UUD NRI 1945. Pada tataran praksis problematika berkenaan dengan ruang lingkup evaluasi raperda, batu uji, bentuk hukum hasil pengujian, tindak lanjut pengujian, dan waktu pengajuan dan pelaksanaan pengujian.Oleh karenanya dibutuhkan rekonstruksi sistem pengujian raperda dan perda agar sesuaidengan amanat UUD 1945. Rekonstruksi berkenaan dengan jenis pengujian raperda dan perda serta hukum acara pengujian.